A Case of Peritoneal Serous Papillary Adenocarcinoma - Minatoya, Go; Takeda, Toshiya; Kohama, Takafumi; Onishi, Ichiro; Hayashi, Yasuo; Kamata, Toru; Michiwa, Yoshio; Koyasaki, Naohiro; Kanno, Masahiro (Nippon Shokaki Geka Gakkai zasshi, 2001)
A 61-year-old woman came to our hospital because of massive ascites upon recommendation from a local clinic. Aspiration cytology showed agglomeration of atypical cells but no primary tumor. Probe laparotomy revealed a tumor resembling serous papillary adenocarcinoma of the ovary in pathological findings, but normal bilateral ovary. Reduction surgery included omentectomy and left oophorectomy. Cisplatin was administered intraperitoneally at surgery and adjuvant chemoterapy was conducted for ovarian cancer postoperatively. Ascites disappeared and serous CA125 levels dropped to normal range. No residual peritoneal tumor was seen in a second-look operation, but atypical cells were still detected in the peritoneal lavage. We added three court chemotherapy there after followed by regular outpatient treatment. No evidence has been found of tumor recurrence for the present.